Kristus Merengkuh Alam Semesta: Gagasan Kristus sebagai Kepala Segala Sesuatu dalam Efesus 1:10, 22 - Tasingkem Tasingkem; Asigor Parongna Sitanggang (Jurnal Teologi Cultivation, 2021)
Abstract:This paper will examine the idea of Christ as the Head of all things in Ephesians 1:10, 22. The idea of Christ as the Head of all things does not contain Christ's dominance over the universe. This idea is panentheism, in the way that Christ is at the same time the Head of the church and of the universe. This idea provides the theological foundation for a missional church. The church's mission is one of the manifestations of missio Dei in this world because this concept teaches the church to direct its mission to the whole world. Keywords: Body of Christ; Christ; head of the church; head of all the things; panentheism; embrace; love; a missionary church Abstrak:Tulisan ini akan mengkaji gagasan Kristus sebagai Kepala segala sesuatu dalam Efesus 1: 10, 22. Gagasan Kristus sebagai Kepala segala sesuatu tidak mengandung dominasi Kristus terhadap alam semesta. Gagasan ini mengandung panenteisme sehingga Kristus sebagai Kepala gereja dan sekaligus segala sesuatu merengkuh alam semesta dalam diri-Nya dengan kasih. Gagasan ini menjadi landasan teologis untuk gereja yang misional. Gereja yang misional menjadi salah satu perwujudan missio Dei di dunia ini karena konsep ini mengajarkan gereja untuk mengarahkan misinya ke seluruh dunia. Kata kunci : Tubuh Kristus; Kristus; Kepala gereja; Kepalasegala sesuatu; panenteisme; merengkuh; kasih; gereja yang misional